STRUKTUR POPULASI TERNAK DOMBA DI LEMBAH PALU - Fatmawati Fatmawati (AgriSains, 2015)
This research was aim to depicting the population structure and produce capacities the sheep livestock in Palu dale, especially in Talise village, Tondo village, and Poboya village. This research has been executed at Februari up to April, 2012. The result of research show that population structure of sheep livestock in research area consisted of the ; adult male 16,70%, adult female 41,01%, young male 7,91%, young female 10,97%, weaning male 4,45%, weaning female 6,23%, male lamb 5,53%, female lamb 7,21%. The birth percentage of sheep livestock 42,00% and the death percentage 2,69% towards population. Based to the amount of the born lamb and the amount of mains which during year 2011, hence harvest lamb in East Palu Subdistrict 50,84%. Natural increase or population accretion of naturally population which obtained 39,30%. To mantain the amount and population structure of the sheep livestock in Palu dale especially in Talise village, Tondo village, and Poboya village is hence needed at last 8 young male livestock and 98 young female livestock as the substitution of unproductive (afkir) sheep mains every year. Key words : Population, population structure, sheep.